2017
DOI: 10.1186/s12944-016-0395-0
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A promotes cholesterol absorption in Caco-2 cells by up-regulation of NPC1L1 expression

Abstract: BackgroundBisphenol A (BPA), an commonly exposed environmental chemicals in humans, has been shown to have a hypercholesterolemic effect with molecular mechanism not clear. Since intestinal cholesterol absorption plays a major role in maintaining total body cholesterol homeostasis, the present study is to investigate whether BPA affects cholesterol absorption in the intestinal Caco-2 cells. Methods: The Caco-2 cells were pretreated with BPA at different concentrations for 24 h and then incubated with radioacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
1
10
0
1
Order By: Relevance
“…Although not tested, several explanations may account for this phenomenon, including that HFD consumption induced increased hepatic TG clearance and/or decreased hepatic TG export. Similarly, increased HDL blood levels, following the consumption of an HFD, was also previously observed ( 29 , 30 ). Nevertheless, HDL levels are not indicators reliable for functionality of this lipoprotein nor the individual atherogenic risk ( 31 ).…”
Section: Discussionsupporting
confidence: 78%
“…Although not tested, several explanations may account for this phenomenon, including that HFD consumption induced increased hepatic TG clearance and/or decreased hepatic TG export. Similarly, increased HDL blood levels, following the consumption of an HFD, was also previously observed ( 29 , 30 ). Nevertheless, HDL levels are not indicators reliable for functionality of this lipoprotein nor the individual atherogenic risk ( 31 ).…”
Section: Discussionsupporting
confidence: 78%
“…For instance, cholesterol absorption in intestine is a multi-step process mediated by specific membrane proteins. The reduction in the permeation of cholesterol can be associated with the regulation of mRNA levels of Niemann-Pick Like 1 protein (NPC1L1) that promotes the transport of cholesterol inside the cells as well as ATP-binding cassette (ABC) proteins such as ABCG5 and ABCG8 which are cholesterol efflux transporters ( Brown and Yu, 2009 ; Feng et al., 2017 ; Jia et al., 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, transporter proteins expression and their activity is regulated by transcriptional as well as post-transcriptional mechanisms. For instance, it is known that EZ, drug used to treat hypercholesterolemia, inhibits Niemann-Pick C1-like 1 (NPC1L1) and mediates cellular cholesterol uptake ( Feng et al., 2017 ; Nakano et al., 2020 ). Furthermore, in the intestine, Liver X Receptors LXRs limits cholesterol absorption by downregulating NPC1L1 ( Duval et al., 2006 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that BPA enhances hepatic cholesterol biosynthesis via increased expression of sterol regulatory element-binding protein 2, which is a key regulator in cholesterol biosynthesis. BPA also promotes cholesterol absorption in the intestinal cells [50,56]. Recent epidemiological and animal studies have suggested that BPA is involved in the development of obesity, type 2 diabetes, and cardiovascular diseases.…”
Section: Genetic Regulation Of Lipid and Glucose Homeostasismentioning
confidence: 99%